Biofuel Cell Based on Anode and Cathode Modified by Glucose Oxidase. Issue 12 (29th November 2013) - Krikstolaityte, Vida; Oztekin, Yasemin; Kuliesius, Jurgis; Ramanaviciene, Almira; Yazicigil, Zafer; Ersoz, Mustafa; Okumus, Aytug; Kausaite‐Minkstimiene, Asta; Kilic, Zeynel; Solak, Ali Osman; Makaraviciute, Asta; Ramanavicius, Arunas
Abstract A single compartment biofuel cell (BFC) based on an anode and a cathode powered by the same fuel glucose is reported. Glucose oxidase (GOx) from Aspergillus niger was applied as a glucose consuming biocatalyst for both anode and cathode of the BFC. The 5‐amino‐1, 10‐phenanthroline modified graphite rod electrode (GRE) with cross‐linked GOx was used as the bioanode, and the GRE with co‐immobilised horseradish peroxidase and GOx was exploited as the biocathode of the BFC. The open‐circuit voltage of the designed BFC exceeded 450 mV and a maximal power density of 3.5 µW/cm2 was registered at a cell voltage of 300 mV.